Effects of honey, glucose, and fructose on the enamel demineralization depth - Fatemeh Ahmadi-Motamayel; Loghman Rezaei-Soufi; Leila Kiani; Mohammad Yousef Alikhani; Jalal Poorolajal; Masoud Moghadam (Elsevier, 2013)
Background/purpose: Caries prevention is an important strategy in many countries. Honey has antibacterial activity against cariogenic bacteria and therefore may have less caries activity than other sugars. This study was conducted to compare the cariogenic effect of honey with those of glucose and fructose. Materials and methods: In this in vitro study, 36 extracted caries-free human premolars were collected and prepared following a multistage laboratory process. Then, the teeth were randomly divided into three groups. Each group was put into separate tubes containing different solutions of honey, fructose, and glucose in a brain-heart infusion broth environment. About 1.5 × 108 cells of Streptococcus mutans (equal to 0.5 McFarland units) were added to each tube. Every other day, 2 ml of the solution were replaced by 2 ml of a previously prepared solution for 21 days. Teeth were sectioned buccolingually using a diamond-saw microtome. The demineralization depth of each section was measured at three points, and the average of three representative measurements was considered the lesion depth. Results: Mean ± SD demineralization depths related to honey, glucose, and fructose were 160.1 ± 59.82 μm, 245.98 ± 96.13 μm, and 195.98 ± 47.53 μm, respectively. Differences among the three means were statistically significant. Conclusion: The results of this study demonstrated that honey had less caries activity than the other sugars. However, further evidence is required to detect the active components and mechanisms by which it reduces demineralization and to demonstrate whether this food has any clinical application for preventing and reducing dental caries.